Enhanced permeability transition explains the reduced calcium uptake in cardiac mitochondria from streptozotocin-induced diabetic rats - Oliveira, Paulo J. (2003)
Cardiac dysfunction is associated with diabetes. It was previously shown that heart mitochondria from diabetic rats have a reduced calcium accumulation capacity. The objective of this work was to determine whether the reduction in calcium accumulation by cardiac mitochondria from diabetic rats is related to an enhanced susceptibility to induction of the mitochondrial permeability transition. Streptozotocin-induced diabetic rats were used as a model to study the alterations caused by diabetes in the permeability transition, 21 days after streptozotocin administration. Heart mitochondria were isolated to evaluate respiratory parameters and susceptibility to the calcium-dependent permeability transition. Our results show that streptozotocin diabetes facilitates the mitochondrial permeability transition in cardiac mitochondria, resulting in decreased mitochondrial calcium accumulation. We also observed that heart mitochondria from diabetic rats had depressed oxygen consumption during the phosphorylative state. The reduced mitochondrial calcium uptake observed in heart mitochondria from diabetic rats is related to an enhanced susceptibility to the permeability transition rather than to damage to the calcium uptake machinery.